The Role Of Nursing And Psychology In Emergency Healthcare (The Review of Diabetic Studies, 2024)
Emergency care environments are known for having a lot of psychological stress, quick decision-making timeframes, and very unwell patients. It is essential to integrate nursing practice with psychological principles to deliver comprehensive and person-centered care in these settings. This research examines the collaborative roles of emergency department psychologists and nurses, concentrating on the assessment and management of acute psychological crises alongside physiological emergencies. Some of the most important topics are the function of emergency nurses, how trauma and disease affect the mind, how important it is to work in teams with people from different fields, and how working in an emergency affects healthcare personnel' mental health. The review talks about some of the common problems that make it hard to provide psychological care in emergencies, such as time restrictions, not enough mental health resources, and not enough training. Early psychological intervention, good communication, and working together as a team can all help improve patient outcomes, safety, and long-term mental health problems. To make emergency care better and more long-lasting, we need to adopt a multi-pronged strategy. This means working together closely between psychiatric services and nursing, as well as getting more targeted instruction and support from institutions. This investigation makes it evident that emergency care models need to be more complete if they want to consider the emotional and physical health of patients.